Study of the Potential of Kuta Mandalika Beach Geochology on Central Lombok District - Nilawati, Nilawati; Umar, Genius (Science and Environmental Journal for Postgraduate, 2019)
This study aimed to analyze the geo ecological potential of the coast in Central Lombok Regency. The research method used a survey method by determining the sample by purposive sampling. The analysis unit used was a geo ecological unit that was assessed for the potential and constraints of each to develop certain tourism activities. Assessment of potential used a SWOT analysis (strength, weakness, opportunity, and threat) to determine the development of coastal areas as opportunities for surrounding communities and sustainable maintenance of resources. The development of tourist areas was able to contribute to local revenues, open business opportunities and employment opportunities and at the same time function to maintain and preserve natural and biological wealth. Classification of geo ecological units in the central Lombok coast were: (1) coastal alluvial geo economic units, (2) valley geo ecological units between hills, and (3) geo ecological units of the slopes of the denudation hills.